2020
DOI: 10.3390/app10062039
|View full text |Cite
|
Sign up to set email alerts
|

GIS-Based Gully Erosion Susceptibility Mapping: A Comparison of Computational Ensemble Data Mining Models

Abstract: Gully erosion destroys agricultural and domestic grazing land in many countries, especially those with arid and semi-arid climates and easily eroded rocks and soils. It also generates large amounts of sediment that can adversely impact downstream river channels. The main objective of this research is to accurately detect and predict areas prone to gully erosion. In this paper, we couple hybrid models of a commonly used base classifier (reduced pruning error tree, REPTree) with AdaBoost (AB), bagging (Bag), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 94 publications
(52 citation statements)
references
References 128 publications
2
47
0
Order By: Relevance
“…Although the literature has mostly reported on the effectiveness of the ensemble techniques, these techniques showed different performances for different problems in different areas. For example, Nhu et al [36] showed that reduced error pruning tree (REPT) performed better in combination with RSS than the bagging and AdaBoost techniques for gully erosion prediction, whereas Pham et al [92] reported that the REPT model performed better with rotation forest and bagging than its combination with the RSS and multiboost for landslide prediction. Different results have also been reported for flood prediction based on the ensemble models [93,94].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the literature has mostly reported on the effectiveness of the ensemble techniques, these techniques showed different performances for different problems in different areas. For example, Nhu et al [36] showed that reduced error pruning tree (REPT) performed better in combination with RSS than the bagging and AdaBoost techniques for gully erosion prediction, whereas Pham et al [92] reported that the REPT model performed better with rotation forest and bagging than its combination with the RSS and multiboost for landslide prediction. Different results have also been reported for flood prediction based on the ensemble models [93,94].…”
Section: Discussionmentioning
confidence: 99%
“…The name bagging is derived from bootstrap aggregating, which is one of the first, most intuitive, and simple ensemble-based algorithms with excellent performance [34][35][36][37]. The diversity of classifiers is received through bootstrap copies of the training dataset.…”
Section: Baggingmentioning
confidence: 99%
“…In general, the regions with higher SPI and STI values have higher potential for groundwater occurrence because they have higher water table [29]. River density presents the drainage capacity which is inverse proportionality of the soil infiltration [10,30,31]. Rainfall is one of the most important factors in groundwater potential model because the more precipitation region are likely to have more groundwater potential [9].…”
Section: Data Usedmentioning
confidence: 99%
“…These results are in line with previous works that demonstrated the advantages of ensemble modeling approaches over single simple modeling. For example, J48 decision tree integrated with Bagging [97] and Naïve Bayes tree integrated with Random Subspace [98] for landslide prediction, RF integrated with different ensemble techniques for gully erosion [31], and alternating decision tree integrated with AdaBoost [29], fisher's linear discriminant function integrated with Bagging [99], RF integrated with Random Subspace [14], and decision stump with different ensemble techniques for groundwater potential mapping [100]. (3), and RMSE (0.504) ( Table 2).…”
Section: Model Performancementioning
confidence: 99%
“…This problem has been addressed through the development and application of machine learning algorithms, which are able to handle large volumes of non-linear and complex data derived from different sources and reported at a variety of scales. These algorithms have been extensively used in natural hazard studies, for example: flooding [23][24][25][26][27][28][29][30][31][32][33], wildfire [34,35], dust storm [36], sinkhole formation [37], drought [38,39], earthquakes [40,41], gully erosion [42][43][44], land/ground subsidence [45,46], groundwater contamination [26,[47][48][49][50][51], and landslides [17,. They can extract informative patterns in historical data to predict future events [79].…”
Section: Introductionmentioning
confidence: 99%